Hubungan Kemandirian Lansia dalam Pemenuhan Kebutuhan Dasar dengan Kualitas Hidup di Yayasan Uma Kandung Banjarmasin - Malinda Ayu Sri Melati; Agustina, Anita; Afriyanti, Uni (PPNI UNIMMAN, 2025)
Elderly life is characterized by a decline in biological, psychological, and social functions. This condition often limits the ability of the elderly to meet basic needs independently, which ultimately can affect their quality of life. Independence in daily activities is a crucial factor because it is directly related to physical and psychological well-being. A good quality of life in the elderly reflects not only physical health but also social, emotional, and environmental aspects. Therefore, research on the relationship between elderly independence and quality of life is important, especially for elderly people living in social institutions such as the Uma Kandung Foundation in Banjarmasin. This study used a quantitative approach with a cross-sectional design. The study sample consisted of 110 elderly people selected using a purposive sampling technique. The instruments used included the Katz Index questionnaire to measure the level of independence of the elderly in meeting basic needs, and the WHOQOL-BREF to assess quality of life. Data were analyzed using the Spearman Rank test to examine the relationship between the two variables. The results showed that the majority of elderly respondents were in the partially dependent category (76.4%), while the quality of life of the majority of respondents was in the sufficient category (75.5%). The Spearman Rank test yielded a significance value of p = 0.000 with a correlation coefficient of r = -0.665, indicating a significant relationship between elderly independence in meeting basic needs and quality of life. A negative relationship indicates that the lower the elderly's dependency or the higher their level of independence, the better their quality of life. The conclusion of this study is that independence in meeting basic needs plays a significant role in the quality of life of the elderly.